Animasi Nyi Roro Kidul Melalui Augmented Reality Upaya Melestarikan Budaya Cerita Rakyat - Magenta, Evan Arwagavin; Kurniawan, Rendya Adi; Muslihah, Isnawati; Rachman, Anung (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
With the rapid development of technology nowdays, the culture we have also needs to adapt to the rapid change of the technology so the culture stays relevant. One of the interesting modern technologies is the Augmented Reality technology where the virtual world able to enters the real world. With AR technology delivering local culture will be more interesting, one of them is Upacara Labuhan which is related to Nyi Roro Kidul. With Augmented Reality technology can emerge a figure of Nyi Roro Kidul into reality through animation. The virtual show of Nyi Roro Kidul is made for preserving the culture of Southern Seas Ruler myth. The method used for the research is MDLC (Media Development Life Cycle) for designing animation from start to finish. Then an interview conducted to determine whether the quality of the animations was sufficient to be distributed. Many opinions say that the style of animation is suitable for audience especially children.